2018
DOI: 10.1186/s12889-018-5615-2
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor air pollution, green space, and cancer incidence in Saxony: a semi-individual cohort study

Abstract: BackgroundThere are a few epidemiological studies that (1) link increased ambient air pollution (AP) with an increase in lung cancer incidence rates and (2) investigate whether residing in green spaces could be protective against cancer. However, it is completely unclear whether other forms of cancer are also affected by AP and if residential green spaces could lower cancer incidence rates in general. Therefore, the objective was to estimate whether AP and green space are associated with several cancer types.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 50 publications
(44 reference statements)
3
112
0
4
Order By: Relevance
“…NO 2 and PM 10 concentrations were significantly and positively associated with the breast cancer incidence rate in South Korean female population. This result is consistent with previous studies that reported significantly higher risk of breast cancer incidence 5,7,9,11 , and is partly consistent with studies that reported suggestive 6,8,10,12,14,15,27 or null 11,[21][22][23]28 associations between air pollutants and breast cancer. Our study adds evidence of a significant positive association to the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…NO 2 and PM 10 concentrations were significantly and positively associated with the breast cancer incidence rate in South Korean female population. This result is consistent with previous studies that reported significantly higher risk of breast cancer incidence 5,7,9,11 , and is partly consistent with studies that reported suggestive 6,8,10,12,14,15,27 or null 11,[21][22][23]28 associations between air pollutants and breast cancer. Our study adds evidence of a significant positive association to the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
“…Incorporating more cases or expanding the cohort population may clarify the evidence, though such efforts would demand resources. There also were ecological studies on the association between breast cancer and air pollution 5,7,9 . Chen et al 5 and Wei et al 9 aggregated air pollutant emission data and age-adjusted breast cancer incidence rates in Surveillance, Epidemiology, and End Results Program of the United States National Cancer Institute that covered 199 counties and approximately 100,000 or less female population and found positive correlations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we accounted for major established or putative risk factors such as body weight, smoking habits, hormone replacement therapy/oral contraceptive use, and partially lack of physical activity, and alcohol intake (64-67) by using the most adjusted estimates from included studies. However, we acknowledge that unmeasured confounding may still have influenced these findings, with reference to environmental risk factors such as cadmium (68)(69)(70), pesticides (71)(72)(73) or air pollution (74)(75)(76)(77). Moreover, food frequency questionnaires used for acrylamide intake estimation in the included studies did not generally collect information about cooking methods, potentially affecting the reliability of exposure assessment (78) and contributing to heterogeneity in results.…”
Section: Discussionmentioning
confidence: 99%
“…Der Endpunkt Kanzerogenität wurde auch in epidemiologischen Studien und Metaanalysen analysiert [113][114][115][116][117]. Auch in diesen Studien ist die NO 2 -Konzentration als Marker für Verkehrsemissionen zu verstehen, so dass die zum Teil gefundenen signifikanten Assoziationen zu erhöhten NO 2 -Konzentrationen für die ursächliche Bewertung nicht herangezogen werden können.…”
Section: Mutagenität Und Kanzerogenitätunclassified